Treatment of acute aluminum toxicity due to alum bladder irrigation in a hemodialysis patient: a case report. Issue 1 (31st December 2022) - Loughran, David; Calello, Diane; Nelson, Lewis
Abstract: Acute aluminum toxicity is encountered rarely in clinical practice but carries a high risk for morbidity and mortality. Despite this risk, our understanding of aluminum toxicity and its treatment is relatively limited. Due to decreased clearance, patients with renal failure have increased risk for significant aluminum-related central nervous system (CNS) toxicity. Medical advances have limited chronic aluminum exposure in these patients, but they are still at increased risk for acute toxicity from certain aluminum-based interventions such as alum bladder irrigation. We report a case of an 87-year-old man with end-stage renal disease on hemodialysis who developed acute aluminum toxicity from alum bladder irrigation. He was treated with daily deferoxamine infusions followed by dialysis with subsequent resolution of his encephalopathy. This case report uniquely documents trending of blood aluminum concentration (blood [Al]) during treatment providing insight into how aluminum blood concentrations shift during chelation therapy.